2019
DOI: 10.1007/s12178-019-09587-x
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Injury and the Anterolateral Complex of the Knee—Importance in Rotatory Knee Instability?

Abstract: Purpose of Review In the setting of rotatory knee instability following anterior cruciate ligament (ACL) reconstruction, there has been a resurgence of interest in knee's anterolateral complex (ALC). Reconstruction or augmentation of the ALC with procedures such as a lateral extra-articular tenodesis (LET) has been proposed to reduce rotatory knee instability in conjunction with ACL reconstruction. The current review investigates the recent literature surrounding the role of the ALC in preventing rotatory knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Besides numerous studies analyzing the ALL, little knowledge exists about the injury incidence of the deep portion of the ITT. This is somewhat surprising, since those structures have been described anatomically much earlier than the ALL, are believed to work as an agonist to the ACL (like a horseshoe) and are emphasized by some authors to play a more important role than the ALL in providing anterolateral rotatory stability [10, 20, 22, 29, 34, 49]. Batty et al [2] examined 50 healthy knees using MRI and identified the dITT in 96% of the cases on sagittal images and 76% in the axial view.…”
Section: Discussionmentioning
confidence: 99%
“…Besides numerous studies analyzing the ALL, little knowledge exists about the injury incidence of the deep portion of the ITT. This is somewhat surprising, since those structures have been described anatomically much earlier than the ALL, are believed to work as an agonist to the ACL (like a horseshoe) and are emphasized by some authors to play a more important role than the ALL in providing anterolateral rotatory stability [10, 20, 22, 29, 34, 49]. Batty et al [2] examined 50 healthy knees using MRI and identified the dITT in 96% of the cases on sagittal images and 76% in the axial view.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to persistent anterolateral rotatory laxity (ALRL), the anterolateral complex (ALC), involving the iliotibial band with its three layers, the accompanying Kaplan fibers, and the anterolateral ligament, has been effectively shown to offer resistance against internal rotational torques, particularly at greater levels of knee flexion [38][39][40][41][42][43][44]. As the tibial insertion of these structures is located at Gerdy's tubercule or slightly posterior to it [38,41,43,45], it is in conflict with the standardized anterolateral approach to the tibial plateau.…”
Section: Discussionmentioning
confidence: 99%